2002
DOI: 10.1029/2001jd000782
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical modeling of the 1999–2000 Arctic winter: 1. Polar stratospheric clouds, denitrification, and dehydration

Abstract: The freezing processes that may lead to the formation of solid phase polar stratospheric clouds (PSCs) have been examined to assess their winter‐long effects, especially denitrification, in a coupled microphysical/photochemical model. Trajectory simulations spanned from November 1999 to April 2000, using a large set of trajectories which provided representative coverage of the entire Arctic vortex through the period of PSC formation and ozone depletion. A freezing process occurring at temperatures above the ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(159 citation statements)
references
References 67 publications
11
147
1
Order By: Relevance
“…Subsequent modelling studies have indicated that the sedimentation of these large NAT particles was capable of causing denitrification comparable to that observed Drdla et al, 2002). Mann et al (2003) used the microphysical DLAPSE model to demonstrate that this mechanism may have caused denitrification in a number of other cold Arctic winters of the 1990s.…”
Section: S Davies Et Al: Model and Mipas-observed Arctic Denitrificmentioning
confidence: 99%
“…Subsequent modelling studies have indicated that the sedimentation of these large NAT particles was capable of causing denitrification comparable to that observed Drdla et al, 2002). Mann et al (2003) used the microphysical DLAPSE model to demonstrate that this mechanism may have caused denitrification in a number of other cold Arctic winters of the 1990s.…”
Section: S Davies Et Al: Model and Mipas-observed Arctic Denitrificmentioning
confidence: 99%
“…Large nitric acidcontaining particles (10 to 20 µm diameter) at low number concentrations (between 10 −5 and 10 −3 cm −3 ) were measured by the NOAA NO y instrument aboard the NASA ER-2 aircraft in the 1999/2000 winter Arctic vortex and have generally been inferred to be NAT (Fahey et al, 2001;Northway et al, 2002a). Previous model calculations Drdla et al, 2002) show that meteorological conditions in the 1999/2000 Arctic vortex allowed NAT particles to grow to the very large sizes that were observed. These large particles can very efficiently denitrify the lower stratosphere on the timescale of a few days (Fahey et al, 2001;Mann et al, 2002;Northway et al, 2002b;Davies et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Stratospheric variations in aerosol optical depth can significantly affect heterogeneous chemistry that leads to ozone depletion because particle surface areas are directly proportional to the optical depth. Below we consider how the continuous presence of volcanic cloudy-like conditions in the Arctic can affect springtime ozone loss processes (13)(14)(15)(16)(17)(18) in a cold year such as the winter of 1999-2000.…”
Section: Volcanic Aerosol Effectsmentioning
confidence: 99%
“…We increased sulfate volume mixing ratio (29) in the model from 0.17 ppbv (nonvolcanic) to 20 ppbv (volcanic) to account for volcanic aerosol effects on ozone. We used the Integrated MicroPhysics and Aerosol Chemistry on Trajectories (IMPACT) model in a quasi-three-dimensional mode (15,16) to obtain the results shown. Nearly 3,000 initial points were distributed evenly (in both horizontal and vertical directions) inside the Arctic vortex on Jan. 15, 2000 between Ϸ450 and 700 K surface.…”
Section: Volcanic Aerosol Effectsmentioning
confidence: 99%
See 1 more Smart Citation